Correlação de longo alcance em séreis temporais do furto de veículo e roubo de veículo de Salvador‐BA: uma aplicação utilizando o DFA e DCCA - Silva Filho, Aloisio Machado da (2011)
In this work we identify long‐range correlations (individual and cross) by DFA and DCCA methods, in the daily records of vehicle theft in Salvador, Bahia, Brazil, from 2003 to 2009. In this study we also identify seasonal components.